2008
DOI: 10.2174/187152008785914752
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Anti-Carcinoma and Anti-Acute Myeloblastic Leukemia Agent, AG490

Abstract: Proteins with tyrosine kinase activity are recognized as key regulators of cellular processes including growth and differentiation. Tyrosine kinase receptors e.g. EGFR and soluble tyrosine kinase proteins e.g. JAK-2, have emerged as essentials in cell survival for cervical carcinoma and acute myeloblastic leukemia, respectively. These receptors and soluble cytoplasm networks have been studied in detail and finally pharmacological agents, targeted at key molecules, could be produced. Tyrphostins are kinases inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Additionally, in vitro studies have demonstrated that STAT3 potentiates anti-apoptotic signals through the induction of Bcl2 and the inhibition of Caspase3 protein expression [15,16,51]. AG, a JAK2-specific inhibitor, has been used to inhibit the phosphorylation of STAT3 in many experimental studies [8,35]. We used 1-lM AG to investigate the role of the JAK2/STAT3 pathway in mediating Cur posttreatment protection against myocardial IR injury.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vitro studies have demonstrated that STAT3 potentiates anti-apoptotic signals through the induction of Bcl2 and the inhibition of Caspase3 protein expression [15,16,51]. AG, a JAK2-specific inhibitor, has been used to inhibit the phosphorylation of STAT3 in many experimental studies [8,35]. We used 1-lM AG to investigate the role of the JAK2/STAT3 pathway in mediating Cur posttreatment protection against myocardial IR injury.…”
Section: Discussionmentioning
confidence: 99%
“…75 IL-15 can lower the proapoptotic Bid protein in LGL leukemia, which was shown to result from increased proteasomal degradation, whereas the induction of Bid by the proteasome inhibitor bortezomib increased leukemic cell death, suggesting that proteasome inhibitors could be an effective treatment option for this disease. 36 Furthermore, a formulation of a proteasomal inhibitors provides long-term disease-free survival in leukemic mice, 49 thus offering a new approach to treating patients with aggressive LGL leukemia.…”
Section: Critical Analysis Of the Potential For Targeting Il-15 In Camentioning
confidence: 99%
“…Recently, the JAK2 inhibitors CEP-33779 and SB1578 were investigated in an RA model (22,23). AG490 has been widely used as a JAK2 inhibitor in various settings, and it appears to specifically suppress JAK2/STAT3 signaling (24)(25)(26)(27). However, its therapeutic potential in autoimmune arthritis has never been addressed.…”
mentioning
confidence: 99%